Chronicle of a meeting: interview with Barbara Heliodora in 2007 (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This text is an interview with the professor, translator, and theater critic Barbara Heliodora (1923-2015), held in person at her home in Rio de Janeiro, in February 2007, for an American magazine. The interview covered themes concerning theater in Rio de Janeiro in 2007,  performing arts education at the university and   modes of production. We consider that this is a historical document, and its publication is a rescue of the memory of the Rio de Janeiro/Brazilian theatre between centuries.
Keywords: Barbara Heliodora; Theatre criticismo; 20th Century; Rio de Janeiro